Cultural ecosystem services enabled through work with shellfish. (October 2021) - Michaelis, Adriane K.; Walton, William C.; Webster, Donald W.; Shaffer, L. Jen
Abstract: Cultural ecosystem services are understudied relative to other types of ecosystem services. This is especially true as they relate to bivalve shellfish. Approaching cultural services through shellfish-based livelihoods, this study utilized ethnographic field methods to detail the benefits received and enabled by individuals through work with shellfish. A total of 218 shellfish growers, wild harvesters, and others working in roles that support shellfisheries in the United States regions of Chesapeake Bay, Gulf of Mexico, and New England were interviewed to create a list of shellfish-enabled cultural, provisioning, regulating, and supporting ecosystem services as well as their related benefits. Results illustrated that individuals involved in both wild and aquaculture shellfisheries perceive and receive similar benefits, though the interpretation of these benefits may vary depending on industry role. In addition to describing benefits overall, attention was given to linked services as well as how services may be enhanced or diminished with a changing social-ecological system. The comprehensive dataset is useful for understanding the myriad benefits associated with shellfisheries and provides the foundation necessary for continued research and analysis of shellfish-associated services. Findings underscore the importance of cultural services relative to their noted absence in shellfish management and policy discussions and, ultimately, policy decisions. Beyond shellfisheries, the study showcases the combined utility of a participatory approach and flexible framework with which to describe cultural services. Highlights: Participatory study of US shellfisheries along Atlantic and Gulf coasts. First comprehensive list of cultural ecosystem services from bivalve shellfish. Work in shellfish aquaculture and wild shellfisheries enable similar benefits. Perception of changing benefits/services varies with participant perspective.